2018
DOI: 10.1002/mrm.27443
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependence and decay characteristics of T2* relaxation in the human meniscus studied with 7 Tesla MR microscopy and compared to histology

Abstract: Purpose To evaluate: (1) the feasibility of MR microscopy T 2 * mapping by performing a zonal analysis of spatially matched T 2 * maps and histological images using microscopic in‐plane pixel resolution; (2) the orientational dependence of T 2 * relaxation of the meniscus; and (3) the T 2 * decay characteristics of the meniscus by statistically evaluating the quality of mono‐ and biexponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Proper setup of sequence parameters, overcoming increased B 0 and B 1 inhomogeneities, and increased RF power deposition using dedicated coils at 7T was necessary to gain higher SNR at 7T versus 3T, as expected. Hager et al 27 used a micro-MRI insert at 7T to investigate the orientation dependence of T 2 ∗ in the knee meniscus. With a resolution approximately 100 times higher than that which is used clinically, they were able to describe the meniscal structures and the strong dependence of T 2 ∗ values on orientation toward B 0 .…”
Section: Quantitative Mrimentioning
confidence: 99%
“…Proper setup of sequence parameters, overcoming increased B 0 and B 1 inhomogeneities, and increased RF power deposition using dedicated coils at 7T was necessary to gain higher SNR at 7T versus 3T, as expected. Hager et al 27 used a micro-MRI insert at 7T to investigate the orientation dependence of T 2 ∗ in the knee meniscus. With a resolution approximately 100 times higher than that which is used clinically, they were able to describe the meniscal structures and the strong dependence of T 2 ∗ values on orientation toward B 0 .…”
Section: Quantitative Mrimentioning
confidence: 99%
“…In a previous study on human menisci, it was shown that the combination of ultra‐high field strength 7 T, an MR microscopy system and a 3D variable echo time sequence meets these requirements for ultra‐short echo times and microscopic resolution 24 and as such represents an ideal, unique setup for the angle‐dependent MR examination of tendons and their respective T 2 * characteristics, which we wish to demonstrate in this study.…”
mentioning
confidence: 84%
“…UHF MRI also allows T2* quantification of the meniscal ultrastructure with a demonstrated relationship between T2* decay and collagen fibres orientation. Although further studies are needed to transfer this method into the clinical practice, these results might help in the interpretation of T2 and T2* quantitative images of early meniscal degeneration at clinical field strengths with lower resolution [ 65 ]. Important information on disc ultrastructure and degeneration was obtained ex vivo with a correlation between matrix degeneration and distribution of PG diffusivity and PG CEST.…”
Section: Menisci and Intervertebral Discsmentioning
confidence: 99%